Multivocal Didaktik Modelling in Early Childhood Education-For a Sustainable Future in a World of Change - Ann-Christine Vallberg Roth; Linda Palla (MDPI AG, 2023)
In times of democratic decline, unanimous choices and approaches and the idea of a singular best practice may be less conducive to democracy and sustainability. Therefore, the aim of this study is to suggest a multivocal approach to education and teaching by studying the question of what may characterise teaching in preschool for a sustainable future. The knowledge contribution and originality of the article is evident in the introduction, method, and results. In abductive analyses, models can summarize what we need to know and teach in pursuit of the creation of open life chances for every child. The results show that didaktik models are open and can provide support for teachers and leaders to consider and base informed decisions on, as well as to motivate their didaktik choices based on scientific foundations and proven experiences. Multivocal didaktik mo-delling intends to open up teaching-cultivating collaboration in preschool for a sustainable future in a world of change. In conclusion, we recommend cultivating an orientation (1) between knowledges, values and didaktik/education/special education in the pursuit of the creation of conditions for good education for all children; (2) between teaching realities and scientific foundations, which are founded in a critical-reflective didaktik, with a choice of direction in relation to an uncertain future; and (3) between continuity, progression and teaching adventures-which can include consolidating, deepening, broadening, raising, and cultivating knowledge and values for multivocality, democracy and sustainability in teaching realities. In the future the concept of multivocal didaktik modelling can be studied in relation to complex teaching realities as in a teaching universe or a teaching multiverse.